Petrology of the eclogites from western Tasmania: Insights into the Cambro-Ordovician evolution of the paleo-Pacific margin of Gondwana - Palmeri, R; Chmielowski, RM; Sandroni, S; Talarico, F; Ricci, CA (Lithos, 2009)
Eclogite facies rocks along the Paleozoicactive margin of Gondwana are rare. They are limited to isolated segments of Northern Victoria Land (Antarctica), western Tasmania, and southeastern Australia. New petrological data for mafic rocks and their host garnet-kyanite schists from the Franklin Metamorphic Complex (western Tasmania) permit reconstruction of six main stages of mineral growth for the eclogite. Stages I and II occurred at greenschist/amphibolite-facies conditions (ca. 500-600 degrees C; 0.55-0.7 GPa for stage II) before attaining high-pressure conditions (at approximate to 600-650 degrees C; > 1.5 GPa for stage III). The following stages, Wand V, record the decompression from high-pressure conditions to amphibolite-facies (ca. 500-600 degrees C; 0.4-1.0 GPa). Finally, stage VI represents the late greenschist-facies retrogression. However, the pelitic schist surrounding the eclogite records only the medium-pressure amphibolite-facies stage. The P-T evolution overtime outlines a clockwise path that is quite steep in both the prograde and retrograde segments. The latter shows a nearly isothermal decompression between the eclogite and the high-pressure amphibolite-facies stage IV, which was achieved at deep crustal levels (approximate to 30 km), and a final decrease in both pressure and temperature from deep/ intermediate to shallow crustal levels. with a typical cooling-unloading path. The lack of a complete re-equilibration during the different stages and the high dP/dT for both the prograde and retrograde paths are indicative of a rapid burial and initially rapid exhumation. The similarity of the mafic whole-rock chemical composition. including N, T to E-MORB and of the peak metamorphic age (approximate to 500 Ma) between the Tasmanian eclogites and the UHP rocks from Northern Victoria Land, supports the idea that they formed in the context of the same contractional event. However, the different P-T conditions and dP/dT point to different tectono-metamorphic settings for the two sectors of the paleo-Pacific margin of Gondwana during the Ross/Tyennan orogeny.